Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.5194/bg-10-2315-2013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patterns in dissolved organic carbon, major elements and trace metals in boreal headwater catchments: trends, mechanisms and heterogeneity

Abstract: The boreal landscape is a complex, spatio-temporally varying mosaic of forest and mire landscape elements that control surface water hydrology and chemistry. Here, we assess long-term water quality time series from three nested headwater streams draining upland forest (C2), peat/mire (C4) and mixed (C7) (forest and mire) catchments. Acid deposition in this region is low and is further declining. Temporal trends in weather and runoff (1981–2008), dissolved organic carbon concentration [DOC] (1993–2010) and othe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 95 publications
5
86
0
1
Order By: Relevance
“…The long-term mean air temperature in the Svartberget catchment is 1.7°C with minimum and maximum temperatures being -9.5 ± 1.4°C in January and 14.5 ± 1.7°C in July respectively, which provides a longterm mean growing season of *148 days (Oni et al 2013). Long-term mean annual precipitation is 610 ± 109 mm with snow cover lasting for *170 days (Köhler et al 2008).…”
Section: Catchment Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…The long-term mean air temperature in the Svartberget catchment is 1.7°C with minimum and maximum temperatures being -9.5 ± 1.4°C in January and 14.5 ± 1.7°C in July respectively, which provides a longterm mean growing season of *148 days (Oni et al 2013). Long-term mean annual precipitation is 610 ± 109 mm with snow cover lasting for *170 days (Köhler et al 2008).…”
Section: Catchment Descriptionmentioning
confidence: 99%
“…Samples were collected in acid-washed polyethylene bottles and stored frozen before being transported to the laboratory for analysis. Water samples were analyzed in the lab using a Shimadzu 5000 TOC analyzer following common lab protocols as described elsewhere (Köhler et al 2008;Laudon et al 2011Winterdahl et al 2011a;Oni et al 2013 (Ehret et al 2012;Teutschbein and Seibert 2013), and do not agree well with observed time series (Fig. 3a, b), these simulations were not used directly as input to the hydrological model in the present study (Fig.…”
Section: Monitoring Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors have been suggested as drivers of this increasing organic matter trend, from decreasing acidification (Evans et al, 2012;Monteith et al, 2007) changing hydrology and warming climates (Evans, 2005) to increasing ionic strength in soils (Hruška et al, 2009) and changes in land use (Garnett et al, 2000). The specific processes behind these trends are likely to at least partially vary regionally (Oni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%